PENGEMBANGAN ALAT UKUR KECERDASAN EMOSIONAL - Fitri, Nisatul (Peneliti.net, 2023)
In the context of education, emotional intelligence has a significant role in achieving more meaningful educational outcomes. Intellectual intelligence (IQ) contributes only 20% to individual success, while emotional intelligence (EQ) contributes as much as 80% to individual success. This study aims to develop and validate the emotional intelligence scale based on Daniel Goleman's theory by developing a measuring instrument based on previous research using questionnaires distributed online and focus group discussions, expert judgment, validity testing, construct validity, and reliability. A total of 40 students participated in the study using random sampling technique. The results of the study: Item-Total Correlation value of 0.312 – 0.803 (above the limit of 0.3). The results of the EFA analysis yielded a Bartlett KMO value of 0.758 (> 0.05), df 325, and p = 0.001 (significant). The total variance explained on the scale is 73.457%. The reliability of the measuring instrument in this study is 0.942 which is based on the Cronbach Alpha coefficient with a maximum value of 1, which means that the reliability of the measuring instrument is very high.